On the Temperature Distribution in an Air-Ventilated Snow Layer - Yen,Yin-Chao (1982)
The problem of simultaneous heat and mass transfer in a homogeneous snow layer, with one side kept at its initial temperature and the other side with a step temperature increase, was solved for the case of constant through-flow conditions. An experimentally determined effective thermal conductivity function, i.e. Ke = 0.0014 + 0.58 G (where G is dry mass flow rate of air in g/sq cm-s), was employed in the solution. The computed nondimensional temperature distribution agreed quite well with experimental data taken under pseudo-steady state conditions with the exception of the temperature for the lowest flow rate used in the experiment. The pronounced nonlinearity of the temperature distribution was found to be a strong function of the flow rate. For sinusoidal variation of atmospheric pressure, the responding flow in the snow medium was also found to be sinusoidal. In conjunction with the diurnal temperature change, this variation facilitated the process of repeated sublimation and condensation in alternate directions and thereby produced a surface layer of approximately constant snow density. (Author)